Pengaruh Return on Assets, Return on Equity, dan Net Profit Margin Terhadap Pertumbuhan Laba pada Subsektor Bank Swasta Konvesional yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2024 - Nabillah, Luthfia; Tristanto, Triyono Adi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The objective of this quantitative study is to analyze the influence of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on profit growth in the conventional private bank subsector. The approach used is quantitative associative using secondary data obtained from financial statements published on the Indonesia Stock Exchange (IDX). This study uses purposive sampling techniques to produce 24 companies with criteria as research samples. The analysis findings indicate each variable has a different impact on profit growth. Partially, ROA significantly affects profit growth, describing asset turnover as measured by sales volume. Assets that are managed effectively will increase investor confidence in investing so that they can increase profits. On the other hand, ROE has no significant influence, meaning that the amount of the owner's return on capital does not contribute much to the increase in the company's profit can occur due to other factors. However, NPM shows a positive significant influence on profit growth, which shows that the higher the NPM a company has, the greater the profit growth that can be achieved. Then, simultaneously, ROA, ROE, and NPM have been proven to significantly influence profit growth. Information on ROA and NPM can be used as the main indicator to assess the bank's ability to generate profits consistently.